Permeability change index for unstable basement - Jaromińska, Marzena (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
This paper presents the results of analyses of the tendencies in the changes of organic soil permeability under load. Ten samples of peats and gyttjas from the Warmia and Mazury Province were analyzed. The research methodology was described and the e – log k relationship at five load degrees was analyzed. The results of multi-year research on organic soils conducted at the laboratory of the Chair of Geotechnics and Road Engineering at the Faculty of Geodesy, Geospatial and Civil Engineering of UWM (Olsztyn) were used for the analyses. A large spread in the permeability change index value, depending on the soil type and the load degree, was found as a result of the performed analysis. Such results suggest, apart from measuring errors, a very high effect of the microstructure of organic soils on the filtration coefficient value and thus also on the tendencies in the changes of this parameter in the consolidation process. The precise identification of the dependence of the filtration coefficient k on the void ratio e and knowledge of the tendencies in soil permeability changes with changes in the void ratio or porosity will allow the value of the filtration coefficient k at different settlement values to be predicted. It will also enable the determination of permeability based on the initial soil parameters.